Iraq's Counterterrorism Laws Under Scrutiny Unjustified Asset Freezes: Hukum Kontraterorisme Irak di Bawah Pengawasan Pembekuan Aset yang Tidak Dapat Dibenarkan - Al-Rubaie, Samah Hadi (Universitas Muhammadiyah Sidoarjo, 2024)
In response to the terrorist threat posed by ISIS, Iraq implemented legal frameworks aimed at disrupting terrorist financing, including the establishment of a committee to freeze terrorist assets as per international and national laws. This study assesses the effectiveness of these measures through qualitative analysis of legal documents and judicial reviews by the Federal Supreme Court, which found many asset freezes to be unjustified. The findings indicate a need for procedural refinement to ensure fair and effective enforcement, highlighting the challenges of balancing legal integrity with counterterrorism efforts in Iraq. Highlights: Effectiveness: Examines the effectiveness of Iraq's asset freezing against terrorism, identifying practical issues. Judicial Oversight: Highlights the Federal Supreme Court's role in overturning unjustified asset freezes. Legal Refinement: Emphasizes the need to refine procedures to ensure fairness and compliance with international standards. Keywords: Terrorism Financing, Legal Frameworks, Asset Freezing, Judicial Review, Counterterrorism